The concept of human dignity in Cubas legal and socio-political reality - Sultan Hamade; Karin Reiber (Universidade Estadual de Londrina, 2019)
This article aims at giving a detailed explanation of the abstract notion of human dignity in the Cuban revolution.It takes into account both legal and socio-political aspects in order to provide a full picture of the subject. The article has a short historical background as a starting point, in which it will be explained how José Martís 1 words, that are part of the Constitutions Preamble, were embedded in the Constitution of 1976. Amongst the three most prominent heroes of revolutionary Cuba are (A&E TELEVSION NETWORKS, 2018): José Martí, Ernesto Ché Guevara and Fidel Castro Ruz 2 , therefore, some explanation will be given on their notion of dignity, too. Furthermore, it describes how the concept of human dignity is interpreted and how it is implemented by the Cuban revolutionary government and judicial system. The article comes to the conclusion that there are three ways in which Cuba has implemented Martís notion of dignity: through the principles of sovereignty, equality and the development of an alternative political system.